Editorial - Ferraro, Speranzina; De Gregorio, Eugenio; Cicero, Lavinia (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Innovation: the act, the work of innovating, i.e. of introducing new systems, new orders, new methods of production; in a concrete sense, any novelty, change, transformation that radically alters or in any case provokes an effective change in a political or social order, a method of production, a technique, etc. (source: treccani.it). Beginning this editorial with the meaning of the term innovation has a twofold nature. On the one hand, it allows us to highlight a commitment of the three editors to work together for the first time, who, without previous knowledge of each other, have embarked on this task (welcome, no doubt), modifying in some ways the operating methods of each in order to pursue a common goal in a cohesive and coherent manner. On the other hand, innovation is also the common and transversal theme of the articles (columns and essays) that make up this issue: innovation in the study contexts explored (communities and urban peripheries, youth generations in comparison, just to anticipate a few examples), innovation in intervention techniques and methodologies, innovation in theoretical reference models. The reader will see how innovation (even when not stated in the title, the abstract or the body of the writings) will always be the red thread linking the various contributions to this issue of the Quaderni di comunità (which not coincidentally bears the subtitle socio-cultural release 5.0).